Sharks as apex predators in the Late Cretaceous Western Interior Seaway empirically revealed by zinc isotope analyses - Jeremy McCormack; Harry Maisch IV; Martin A. Becker; Michael L. Griffiths; Jade Knighton; Robert A. Eagle; Kevin Stevens; Wolfgang Müller; Kenshu Shimada (Gondwana Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Scaling carbon capture and storage (CCS) to gigaton capacity: A multi-dimensional and critical review - Benjamin Mitterrutzner; Benjamin K. Sovacool; Brage Rugstad Knudsen; Morgan D. Bazilian; Jinsoo Kim; Simon Roussanaly; Asgeir Tomasgard; Steven Griffiths (International Journal of Greenhouse Gas Control, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

What causes energy and transport poverty in Ireland? Analysing demographic, economic, and social dynamics, and policy implications - Christopher Lowans; Aoife Foley; Dylan Furszyfer Del Rio; Brian Caulfield; Benjamin K. Sovacool; Steven Griffiths; David Rooney (Energy Policy, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Warming Stimulates Iron-Mediated Carbon and Nutrient Cycling in Mineral-Poor Peatlands - Holly J. Curtinrich; Stephen D. Sebestyen; Natalie A. Griffiths; Steven J. Hall (Ecosystems, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Resolving the spatial distributions of Dipturus intermedius and Dipturus batis—the two taxa formerly known as the ‘common skate’ - Maisie Bache-Jeffreys; Bárbara Lins Caldas de Moraes; Rachel E. Ball; Gui Menezes; Jónbjörn Pálsson; Christophe Pampoulie; Jamie R. Stevens; Andrew M. Griffiths (Environmental Biology of Fishes, 2021)
Batoid fishes are among the most endangered marine vertebrates, yet conservation efforts have been confounded by incomplete taxonomy. Evidence suggest that the critically endangered ‘common skate’ actually represents two species: the flapper skate ( Dipturus intermedius ) and the blue skate ( Dipturus batis ). However, knowledge of the geographic range of these two nominal species is limited. Here, DNA sequencing is used to distinguish these species, allowing their spatial distributions to be clarified. These records were also used as the basis for species distribution modelling, providing the first broad scale models for each species across the Northeast Atlantic. Samples were obtained from Iceland, the UK (specifically Shetland), the North Sea and the Azores. Results suggest that D. batis was commonly distributed in the Western Approaches and Celtic Sea, extending out to Rockall and Iceland. D. intermedius generally appears to be less abundant, but was most frequent around northern Scotland and Ireland, including the northern North Sea, and was also present in Portugal. Two individuals were also identified from seamounts in remote areas of the Atlantic around the Azores, the furthest south and west the species has been found. This supports reports that the flapper skate historically had a much wider distribution (which was also highlighted in the distribution model), emphasising the large scale over which fisheries may have led to extirpations. Furthermore, these Azorean samples shared a unique control region haplotype, highlighting the importance of seamounts in preserving genetic diversity.

Carbon flux and forest dynamics: Increased deadwood decomposition in tropical rainforest tree‐fall canopy gaps - Hannah M. Griffiths; Paul Eggleton; Nicole Hemming‐Schroeder; Tom Swinfield; Joel S. Woon; Steven D. Allison; David A. Coomes; Louise A. Ashton; Catherine L. Parr (Global Change Biology, 2021)
Tree mortality rates are increasing within tropical rainforests as a result of global environmental change. When trees die, gaps are created in forest canopies and carbon is transferred from the living to deadwood pools. However, little is known about the effect of tree‐fall canopy gaps on the activity of decomposer communities and the rate of deadwood decay in forests. This means that the accuracy of regional and global carbon budgets is uncertain, especially given ongoing changes to the structure of rainforest ecosystems. Therefore, to determine the effect of canopy openings on wood decay rates and regional carbon flux, we carried out the first assessment of deadwood mass loss within canopy gaps in old‐growth rainforest. We used replicated canopy gaps paired with closed canopy sites in combination with macroinvertebrate accessible and inaccessible woodblocks to experimentally partition the relative contribution of microbes vs. termites to decomposition within contrasting understorey conditions. We show that over a 12 month period, wood mass loss increased by 63% in canopy gaps compared with closed canopy sites and that this increase was driven by termites. Using LiDAR data to quantify the proportion of canopy openings in the study region, we modelled the effect of observed changes in decomposition within gaps on regional carbon flux. Overall, we estimate that this accelerated decomposition increases regional wood decay rate by up to 18.2%, corresponding to a flux increase of 0.27 Mg C ha −1 year −1 that is not currently accounted for in regional carbon budgets. These results provide the first insights into how small‐scale disturbances in rainforests can generate hotspots for decomposer activity and carbon fluxes. In doing so, we show that including canopy gap dynamics and their impacts on wood decomposition in forest ecosystems can help improve the predictive accuracy of the carbon cycle in land surface models.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Breaking All the Rules: The First Recorded Hard Substrate Sessile Benthic Community Far Beneath an Antarctic Ice Shelf - Huw J. Griffiths; Paul Anker; Katrin Linse; Jamie Maxwell; Alexandra L. Post; Craig Stevens; Slawek Tulaczyk; James A. Smith (Frontiers in Marine Science, 2021)
The seafloor beneath floating ice shelves accounts roughly a third of the Antarctic’s 5 million km 2 of continental shelf. Prior to this study, our knowledge of these habitats and the life they support was restricted to what has been observed from eight boreholes drilled for geological and glaciological studies. The established theory of sub-ice shelf biogeography is that both functional and taxonomic diversities decrease along a nutrient gradient with distance from the ice shelf front, resulting in a depauperate fauna, dominated by mobile scavengers and predators toward the grounding line. Mobile macro-benthic life and mega-benthic life have been observed as far as 700 km under an ice shelf. New observations from two boreholes in the Filchner-Ronne Ice Shelf challenge the idea that sessile organisms reduce in prevalence the further under the ice you go. The discovery of an established community consisting of only sessile, probably filter feeding, organisms (sponges and other taxa) on a boulder 260 km from the ice front raises significant questions, especially when the local currents suggest that this community is somewhere between 625 km and 1500 km in the direction of water flow from the nearest region of photosynthesis. This new evidence requires us to rethink our ideas with regard to the diversity of community types found under ice shelves, the key factors which control their distribution and their vulnerability to environmental change and ice shelf collapse.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Trajectories of body mass index, from adolescence to older adulthood, and pancreatic cancer risk; a population-based case–control study in Ontario, Canada - Vanessa De Rubeis; Michelle Cotterchio; Brendan T. Smith; Lauren E. Griffith; Ayelet Borgida; Steven Gallinger; Sean Cleary; Laura N. Anderson (Cancer Causes & Control, 2019)

Northern areas as refugia for temperate species under current climate warming: Atlantic salmon ( Salmo salar L.) as a model in northern Europe - Jose L. Horreo; Andrew M. Griffiths; Gonzalo Machado‐Schiaffino; Jamie R. Stevens; Eva Garcia‐Vazquez (Journal of Fish Biology, 2019)
In this work, patterns of geographical genetic diversity in Atlantic salmon Salmo salar were studied across the whole Atlantic Arc; whether these patterns (and thus genetic population structure) were affected by water temperatures was also evaluated. Salmo salar populations were characterized using microsatellite loci and then analysed with reference to ocean surface temperature data from across the region. Analysis showed the presence of a latitudinal cline of genetic variability (higher in northern areas) and water temperatures (sea surface temperatures) determining genetic population structure (the latter in combination with genetic drift in southern populations). Under the current global change scenario, northern areas of Europe would constitute refugia for diversity in the future. This is effectively the inverse of what appears to have happened in glacial refugia during the last glacial maximum. From this perspective, the still abundant and large northern populations S. salar should be considered as precious as the small almost relict southern ones and given appropriate protection. Careful management of the species, coordinated across countries and latitudes, is needed in order to avoid its extinction in Europe.

Shear stress and blood trauma under constant and pulse-modulated speed CF-VAD operations: CFD analysis of the HVAD - Zengsheng Chen; Sofen K. Jena; Guruprasad A. Giridharan; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Medical & Biological Engineering & Computing, 2019)

Herbivory and eutrophication mediate grassland plant nutrient responses across a global climatic gradient - T. Michael Anderson; Daniel M. Griffith; James B. Grace; Eric M. Lind; Peter B. Adler; Lori A. Biederman; Dana M. Blumenthal; Pedro Daleo; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; Andrew S. MacDougall; et al. (Ecology, 2018)
Plant stoichiometry, the relative concentration of elements, is a key regulator of ecosystem functioning and is also being altered by human activities. In this paper we sought to understand the global drivers of plant stoichiometry and compare the relative contribution of climatic vs. anthropogenic effects. We addressed this goal by measuring plant elemental (C, N, P and K) responses to eutrophication and vertebrate herbivore exclusion at eighteen sites on six continents. Across sites, climate and atmospheric N deposition emerged as strong predictors of plot‐level tissue nutrients, mediated by biomass and plant chemistry. Within sites, fertilization increased total plant nutrient pools, but results were contingent on soil fertility and the proportion of grass biomass relative to other functional types. Total plant nutrient pools diverged strongly in response to herbivore exclusion when fertilized; responses were largest in ungrazed plots at low rainfall, whereas herbivore grazing dampened the plant community nutrient responses to fertilization. Our study highlights (1) the importance of climate in determining plant nutrient concentrations mediated through effects on plant biomass, (2) that eutrophication affects grassland nutrient pools via both soil and atmospheric pathways and (3) that interactions among soils, herbivores and eutrophication drive plant nutrient responses at small scales, especially at water‐limited sites.

Understanding and managing fish populations: keeping the toolbox fit for purpose - J. R. Paris; K. D. Sherman; E. Bell; C. Boulenger; C. Delord; M. B. M. El‐Mahdi; E. A. Fairfield; A. M. Griffiths; C. Gutmann Roberts; R. D. Hedger; L. E. Holman; L. H. Hooper; et al. (Journal of Fish Biology, 2018)
Wild fish populations are currently experiencing unprecedented pressures, which are projected to intensify in the coming decades. Developing a thorough understanding of the influences of both biotic and abiotic factors on fish populations is a salient issue in contemporary fish conservation and management. During the 50th Anniversary Symposium of The Fisheries Society of the British Isles at the University of Exeter, UK, in July 2017, scientists from diverse research backgrounds gathered to discuss key topics under the broad umbrella of ‘Understanding Fish Populations’. Below, the output of one such discussion group is detailed, focusing on tools used to investigate natural fish populations. Five main groups of approaches were identified: tagging and telemetry; molecular tools; survey tools; statistical and modelling tools; tissue analyses. The appraisal covered current challenges and potential solutions for each of these topics. In addition, three key themes were identified as applicable across all tool‐based applications. These included data management, public engagement, and fisheries policy and governance. The continued innovation of tools and capacity to integrate interdisciplinary approaches into the future assessment and management of fish populations is highlighted as an important focus for the next 50 years of fisheries research.

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Erratum to: Mechanistic insight of platelet apoptosis leading to non-surgical bleeding among heart failure patients supported by continuous-flow left ventricular assist devices - Nandan K. Mondal; Tieluo Li; Zengsheng Chen; Hegang H. Chen; Erik N. Sorensen; Si M. Pham; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2017)

Mechanistic insight of platelet apoptosis leading to non-surgical bleeding among heart failure patients supported by continuous-flow left ventricular assist devices - Nandan K. Mondal; Tieluo Li; Zengsheng Chen; Hegang H. Chen; Erik N. Sorensen; Si M. Pham; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2017)

Effects of caffeine on alcohol reinforcement: beverage choice, self-administration, and subjective ratings - Mary M. Sweeney; Steven E. Meredith; Daniel P. Evatt; Roland R. Griffiths (Psychopharmacology, 2017)

Population‐level consequences for wild fish exposed to sublethal concentrations of chemicals – a critical review - Patrick B Hamilton; Ian G Cowx; Marjorie F Oleksiak; Andrew M Griffiths; Mats Grahn; Jamie R Stevens; Gary R Carvalho; Elizabeth Nicol; Charles R Tyler (Fish and Fisheries, 2016)
Concentrated chemical spills have been shown to impact adversely on fish populations and even cause localized population extinctions. Evaluating population‐level impacts of sublethal exposure concentrations is, however, complex and confounded by other environmental pressures. Applying effect measures derived from laboratory‐based chemical exposures to impacts in wild fish populations is constrained by uncertainty on how biochemical response measures (biomarkers) translate into health outcomes, lack of available data for chronic exposures and the many uncertainties in available fish population models. Furthermore, wild fish show phenotypic plasticity and local adaptations can occur that adds geographic and temporal variance on responses. Such population‐level factors are rarely considered in the chemical risk assessment process and can probably be derived only from studies on wild fish. Molecular technologies, including microsatellite and SNP genotyping, and RNAS eq for gene expression studies, are advancing our understanding of mechanisms of eco‐toxicological response, tolerance, adaptation and selection in wild populations. We examine critically the application of such approaches with examples including using microsatellites that has identified roach ( Rutilus rutilus ) populations living in rivers contaminated with sewage effluents that are self‐sustaining, and studies of stickleback ( Gasterosteus aculeatus ) and killifish ( Fundulus heteroclitus ) that have identified genomic regions under selection putatively related to pollution tolerance. Integrating data on biological effects between laboratory‐based studies and wild populations, and building understanding on adaptive responses to sublethal exposure are some of the priority research areas for more effective evaluation of population risks and resilience to contaminant exposure.

Activation and shedding of platelet glycoprotein IIb/IIIa under non-physiological shear stress - Zengsheng Chen; Nandan K. Mondal; Jun Ding; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2015)

Long‐term effects of stock transfers: synergistic introgression of allochthonous genomes in salmonids - J. L. Horreo; G. Machado‐Schiaffino; A. M. Griffiths; D. Bright; J. R. Stevens; E. Garcia‐Vazquez (Journal of Fish Biology, 2014)
The genus Salmo was employed as a model to study introgression of genes between species due to secondary contacts. Seven microsatellite loci, the LDH‐C1 * locus and the 5S ribosomal DNA were studied. Results showed the mutually enhanced introgression of allochthonous genomes into southern European salmonids. This phenomenon appears to go beyond a simple consequence of the altered behaviour of domestic individuals. Invasions of autochthonous genomes by allochthonous genes would be enhanced by human activities such as stock transfers, which would simultaneously promote allochthonous and allospecific (from other species) introgressions in a synergistic process in Atlantic salmon Salmo salar and brown trout Salmo trutta . As a minor result, the data do not support the value of the microsatellite locus SsaD486 as a species‐specific marker.

A suggested new bacteriophage genus: “Viunalikevirus” - Evelien M. Adriaenssens; Hans-Wolfgang Ackermann; Hany Anany; Bob Blasdel; Ian F. Connerton; David Goulding; Mansel W. Griffiths; Steven P. Hooton; Elizabeth M. Kutter; Andrew M. Kropinski; Ju-Hoon Lee; Martine Maes; et al. (Archives of Virology, 2012)
We suggest a bacteriophage genus, “Viunalikevirus”, as a new genus within the family Myoviridae . To date, this genus includes seven sequenced members: Salmonella phages ViI, SFP10 and ΦSH19; Escherichia phages CBA120 and PhaxI; Shigella phage phiSboM-AG3; and Dickeya phage LIMEstone1. Their shared myovirus morphology, with comparable head sizes and tail dimensions, and genome organization are considered distinguishing features. They appear to have conserved regulatory sequences, a horizontally acquired tRNA set and the probable substitution of an alternate base for thymine in the DNA. A close examination of the tail spike region in the DNA revealed four distinct tail spike proteins, an arrangement which might lead to the umbrella-like structures of the tails visible on electron micrographs. These properties set the suggested genus apart from the recently ratified subfamily Tevenvirinae , although a significant evolutionary relationship can be observed.

Fault Roughness at Seismogenic Depths from LIDAR and Photogrammetric Analysis - Andrea Bistacchi; W. Ashley Griffith; Steven A. F. Smith; Giulio Di Toro; Richard Jones; Stefan Nielsen (Pure and Applied Geophysics, 2011)

Microsatellite standardization and evaluation of genotyping error in a large multi-partner research programme for conservation of Atlantic salmon (Salmo salar L.) - J. S. Ellis; J. Gilbey; A. Armstrong; T. Balstad; E. Cauwelier; C. Cherbonnel; S. Consuegra; J. Coughlan; T. F. Cross; W. Crozier; E. Dillane; D. Ensing; et al. (Genetica, 2011)

Comparison of patterns of genetic variability in wild and supportively bred stocks of brown trout, Salmo trutta - A. M. GRIFFITHS; D. BRIGHT; J. R. STEVENS (Fisheries Management and Ecology, 2009)

Complete mitochondrial control region sequences indicate a distinct variety of brown trout Salmo trutta in the Aral Sea - A. M. Griffiths; D. Bright; J. R. Stevens (Journal of Fish Biology, 2009)
Complete sequencing of the mtDNA control region (CR) from five specimens of brown trout Salmo trutta from the Amu Darya River identified two novel haplotypes belonging to the Danubian lineage. This finding supports the long‐standing hypothesis that brown trout in the Aral Sea represent a distinct genetic stock and also illustrates the benefits that complete sequencing of the CR can provide for elucidating phylogeographic relationships.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Recovering Quasi-Active Properties of Dendritic Neurons from Dual Potential Recordings - Steven J. Cox; Boyce E. Griffith (Journal of Computational Neuroscience, 2001)

Contributions to composite sampling - Gerald van Belle; William C. Griffith; Steven D. Edland (Environmental and Ecological Statistics, 2001)

Characterization of Aeromonas salmonicida variants with altered cell surfaces and their use in studying surface protein assembly - Steven G. Griffiths; William H. Lynch (Archives of Microbiology, 1990)

Errata - Steven M. Carr; Mitch Griffith (Biochemical Genetics, 1987)

Rapid isolation of animal mitochondrial DNA in a small fixed-angle rotor at ultrahigh speed - Steven M. Carr; O. Mitch Griffith (Biochemical Genetics, 1987)